A new beginning with president Biden: Five German and European prioritites for the transatlantic agenda - Laura von Daniels; Markus Kaim; Ronja Kempin; Kai-Olaf Lang; Marco Overhaus; Johannes Thimm (Stiftung Wissenschaft und Politik (SWP), 2020)
Although Joseph Biden has now been elected 46th president of the United States, transatlantic relations do not automatically revert to their pre-2017 status quo. Too much has changed in the international sphere, too central has great power competition become to the international order. Europe will have to be much more clear than in the past about what it expects from Washington - and what it is prepared to contribute. Berlin and Brussels should work toward a new transatlantic agenda with the Biden administration, with five priorities including joint action against political disinformation and a transatlantic vaccine alliance.
Keywords: 320